Comparison of antibiofilm activity of low-concentrated hypochlorites vs polyhexanide-containing antiseptic - Paleczny, Justyna; Junka, Adam Felix; Krzyżek, Paweł; Czajkowska, Joanna; Kramer, Axel; Benkhai, Hicham; Żyfka-Zagrodzińska, Ewa; Bartoszewicz, Marzenna (Frontiers in Cellular and Infection Microbiology, 2023)
In this work, the antimicrobial/antibiofilm activity of two low-concentrated chlorine-based and releasing solutions was investigated on a total of 78 strains of methicillin-resistant Staphylococcus aureus, Pseudomonas aeruginosa, and Candida albicans, using the cohesive spectrum of in vitro settings, including microtiter plate models, biofilm-oriented antiseptic test, cellulose-based biofilm model, biofilm bioreactors and Bioflux model. The antiseptic containing polyhexamethylene biguanide was used in the character of usability control of performed tests. The results obtained by static biofilm models indicate that low-concentrated chlorine-based and releasing solutions display none to moderate antibiofilm activity, while data obtained by means of the Bioflux model, providing flow conditions, indicate the moderate antibiofilm activity of aforementioned substances compared with the polyhexanide antiseptic. In light of in vitro data presented in this manuscript, the earlier reported favorable clinical results of low-concentrated hypochlorites should be considered rather an effect of their rinsing activity combined with low cytotoxicity but not the antimicrobial effect per se. For the treatment of heavily biofilm-infected wounds, polyhexanide should be considered the agent of choice because of its higher efficacy against pathogenic biofilms.